Diagnostic value of urine soluble triggering receptor expressed on myeloid cells (sTREM-1) for late-onset neonatal sepsis in infected preterm neonates. Issue 4 (April 2018) - Alkan Ozdemir, Senem; Ozer, Esra Arun; Ilhan, Ozkan; Sutcuoglu, Sumer; Tatlı, Mansur
Objective: Sepsis is a complex clinical condition caused by a dysregulated immune response to an infection resulting in a fatal outcome. This study aimed to investigate the value of urine soluble triggering receptor expressed on myeloid cells (sTREM-1) for diagnosing culture-proven sepsis in preterm infants. Methods: Preterm neonates were evaluated for late-onset sepsis (LOS). Laboratory investigations were performed. Urine sTREM-1 samples and blood cultures were synchronously collected. Using blood culture results, preterm neonates were divided into the culture-proven group and suspected sepsis group. Results: A total of preterm 62 infants were included in the study; 31 had culture-proven sepsis and 31 were suspected as having sepsis. There were no significant differences in gestational age, sex, birth weight, and delivery mode between the groups. Neonates in the culture-proven group had significantly higher urine sTREM-1 levels than did those in the suspected sepsis group. Using a cut-off point for a urine sTREM-1 level of 78.5 pg/mL, the sensitivity was 0.90, specificity was 0.78, positive predictive value was 0.68, and negative predictive value was 0.94. Conclusions: The present study highlights the role of urine sTREM-1 levels in LOS. Urine sTREM-1 may be a reliable and sensitive marker in detecting sepsis in preterm infants.